2011
DOI: 10.1007/s10546-011-9640-2
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating Aerodynamic Parameters of Urban-Like Surfaces with Heterogeneous Building Heights

Abstract: There are many geometrical factors than can influence the aerodynamic parameters of urban surfaces and hence the vertical wind profiles found above. The knowledge of these parameters has applications in numerous fields, such as dispersion modelling, wind loading calculations, and estimating the wind energy resource at urban locations. Using quasiempirical modelling, we estimate the dependence of the aerodynamic roughness length and zero-plane displacement for idealized urban surfaces, on the two most significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 46 publications
0
57
0
2
Order By: Relevance
“…This suggests z d can be greater than the average roughness-element height (e.g. Jiang et al 2008;Xie et al 2008;Hagishima et al 2009;Zaki et al 2011;Millward-Hopkins et al 2011;Tanaka et al 2011;Kanda et al 2013), with a peak z 0 up to five times greater and displaced to higher λ f (Hagishima et al 2009;Zaki et al 2011). Roughness-element staggering, orientation and most importantly height heterogeneity therefore need to be considered in morphometric calculations; especially in complex city centres, such as the current study site (Sect.…”
Section: Relations Between Aerodynamic Parameters and Roughness-elemementioning
confidence: 93%
See 2 more Smart Citations
“…This suggests z d can be greater than the average roughness-element height (e.g. Jiang et al 2008;Xie et al 2008;Hagishima et al 2009;Zaki et al 2011;Millward-Hopkins et al 2011;Tanaka et al 2011;Kanda et al 2013), with a peak z 0 up to five times greater and displaced to higher λ f (Hagishima et al 2009;Zaki et al 2011). Roughness-element staggering, orientation and most importantly height heterogeneity therefore need to be considered in morphometric calculations; especially in complex city centres, such as the current study site (Sect.…”
Section: Relations Between Aerodynamic Parameters and Roughness-elemementioning
confidence: 93%
“…However, the correction is not considered here as no basis is provided and z d is not addressed. Kastner-Klein and Rotach's (2004) empirically derived relationship using wind-tunnel results from a scaled physical model of Nantes, France, is also not considered because it does not incorporate λ f , a parameter that is regarded as important (Millward-Hopkins et al 2011;Mohammad et al 2015a). Two morphometric methods that directly incorporate roughness-element height variability are explored: the Mho (Millward-Hopkins et al 2011) and Kan (Kanda et al 2013) methods.…”
Section: Mho Kanmentioning
confidence: 99%
See 1 more Smart Citation
“…in Millward-Hopkins et al (2011) and Kanda et al (2013). The main limitation of these above-mentioned studies is the fact that the suggested correlations y 0 = y 0 (λ F , λ P ) are calculated over a collection of data sets from disparate sources with significantly different boundary conditions and characterised by geometrically different roughness elements.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of these above-mentioned studies is the fact that the suggested correlations y 0 = y 0 (λ F , λ P ) are calculated over a collection of data sets from disparate sources with significantly different boundary conditions and characterised by geometrically different roughness elements. Regardless, amongst the morphometric bulk drag prediction methods, Macdonald's (1998) appears to be widely used as it incorporates a broader range of scenarios when compared to other methods (Grimmond &Oke 1999 andMillward-Hopkins et al 2011). Figure 2(a) shows its prediction for y 0 as a function of λ F and λ P .…”
Section: Introductionmentioning
confidence: 99%